2014
DOI: 10.2108/zs130215
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Ultrastructure of the Salivary Glands of the SpittlebugLepyronia coleopterata(L.) (Hemiptera: Aphrophoridae)

Abstract: We investigated the salivary glands in Lepyronia coleopterata (L.), and found that the salivary glands are paired structures and consist of principal and accessory glands. Each principal gland contains an anterior lobe and a posterior lobe. Three types of acini (I, II, III) are observed in the anterior lobe, whereas the posterior lobe contains only one type of acini (IV). Rhabdus emerges from the middle portion of the acini III and IV. The oval-shaped accessory gland connects with the principal gland via a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…HvTIP2;1, HvTIP2;3, HvNIP1;1, HvNIP1;2), suggesting this residue may be functionally important for water transport of TIPs and NIPs. In line with this suggestion, a recent study observed that HvNIP1;1, HvNIP1;2, HvNIP2;1 and HvNIP2;2 all of which possessed the Val residue in TM2 ( S2 Fig ), were water transporters [ 26 ].…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…HvTIP2;1, HvTIP2;3, HvNIP1;1, HvNIP1;2), suggesting this residue may be functionally important for water transport of TIPs and NIPs. In line with this suggestion, a recent study observed that HvNIP1;1, HvNIP1;2, HvNIP2;1 and HvNIP2;2 all of which possessed the Val residue in TM2 ( S2 Fig ), were water transporters [ 26 ].…”
Section: Resultsmentioning
confidence: 68%
“…Our annotations of HvNIP2;1 and HvNIP2;2 are based on the dates of registration as well as % identities to the other annotated barley sequences (listed in Table 1 ) and to the orthologs in rice [ 37 ], maize [ 7 ] and/or sorghum (SbNIP2;1 - EF373651; SbNIP2;2 - EF408053). Hence we suggest that AB540229 represents HvNIP2;2, and likewise, AB710142 (annotated as HvNIP2;2; 02-APR-2012, Shibasaka et al , direct submission; also see [ 26 ]) represents HvNIP2;1. These suggestions are open to further reports and/or Genbank updates.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In S. castanea , the principal salivary gland is bilobate and the accessory salivary gland is tubular as found in other Pentatomomorpha, suggesting that the anatomy of the salivary glands in this infraorder may be phylogenetically biased other than by feeding habits. The salivary glands in Hemiptera vary in shape, size, and number of lobes (Baptist, 1941; Lacombe, 1999; Kumar & Sahayaraj, 2012; Zhong et al, 2014). Within Cimicomorpha, Triatoma vitticeps Stal, 1859 (Reduviidae) has three types of principal salivary glands (Lacombe, 1999).…”
Section: Discussionmentioning
confidence: 99%